2016
DOI: 10.1097/inf.0000000000001242
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Hand, Foot and Mouth Disease in Asia

Abstract: Context:Hand, foot and mouth disease (HFMD) is a widespread pediatric disease caused primarily by human enterovirus 71 (EV-A71) and Coxsackievirus A16 (CV-A16).Objective:This study reports a systematic review of the epidemiology of HFMD in Asia.Data Sources:PubMed, Web of Science and Google Scholar were searched up to December 2014.Study Selection:Two reviewers independently assessed studies for epidemiologic and serologic information about prevalence and incidence of HFMD against predetermined inclusion/exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
174
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(197 citation statements)
references
References 125 publications
16
174
0
7
Order By: Relevance
“…This is similar with the meta analysis from the papers published in Asia which reported that age and being female were the major risk factors of HFMD [24]. Some studies [25][26][27] reported that age was the main risk factor for HFMD particularly age < 4 years old.…”
Section: Discussionsupporting
confidence: 76%
“…This is similar with the meta analysis from the papers published in Asia which reported that age and being female were the major risk factors of HFMD [24]. Some studies [25][26][27] reported that age was the main risk factor for HFMD particularly age < 4 years old.…”
Section: Discussionsupporting
confidence: 76%
“…EV‐A71 usually causes hand, foot, and mouth disease (HFMD) and herpangina in children younger than 5 years. Typical signs and symptoms of HFMD appear 3 to 7 days after exposure, such as fever, sore throat, mouth ulcers, and rashes on the hands and feet, as virus levels increase in blood (Figure ). Besides EV‐A71, coxsackievirus A16 (CV‐A16) and other enteroviruses including CV‐A4, A5, A6, and A10 are also associated with HFMD .…”
Section: What Is Known About Enterovirus A71mentioning
confidence: 99%
“…Most cases of HFMD and herpangina are mild and self‐limiting, and hospitalization is not required. Up to 71% of children can be asymptomatic …”
Section: What Is Known About Enterovirus A71mentioning
confidence: 99%
“…Being a close relative of poliovirus, EV71 is deemed as an important neurotropic virus worldwide [1]. Since its first isolation in California in 1969, several major outbreaks have been reported in China, Singapore, Korea, and Japan [2][3][4][5]. Although the clinical manifestations are generally mild and self-limiting, including HFMD and herpangina, severe neurological complications have been consistently reported with EV71-associated infections, causing brainstem encephalitis, acute flaccid paralysis, pulmonary edema and cardiopulmonary failure [6,7].…”
Section: Introductionmentioning
confidence: 99%